+0  
 
0
149
1
avatar

thank you 

 Oct 12, 2019
 #1
avatar+111392 
+1

y  =  5 x+1      take the log of both sides

 

log y  =  log 5 x+1      and by a log property we can write

 

log y  = (x + 1) log 5

 

log y  =  x log 5  + log 5

 

log y - log 5  = x log 5      divide both sides by  log 5

 

logy / log5  - 1 =  x        and by another log property we can write

 

log5 y - 1  = x       "swap"  x  and y

 

log 5 x  - 1  =  y

 

g(x)  = log 5 x - 1        this is the inverse.......this answer goes in the first box

 

left         this answer goes in the second box

 

down      this answer goes in the last box

 

 

cool cool cool

 Oct 12, 2019

9 Online Users